Effect of travel speed in arc welding processes using the finite element method (2021)
Welding is a process for joining elements commonly found at an industrial level where one of the most widely used types is the electric arc. For its correct application, variables such as type of electrode, amperage, voltage, travel speed, polarity, type of joint, among others, must be taken into account. In this work, the effect of travel speed was evaluated, which directly affects the mode of metal transfer and the morphology of the weld bead, therefore, it must be correctly defined in order to satisfactorily achieve the union of the materials. To determine its effect, the thermal profile was calculated on a plate using a finite element software. The speed values used were taken from specifications recommended by industrial suppliers of welding consumables. Furthermore, the simulation was performed for a butt joint, where it was assumed that the energy applied to the metal was uniform and constant over a circular area.